Highly resistant methanogenic archaea from Siberian permafrost as candidates for the possible life on Mars - Morozova, Daria; Wagner, Dirk (2006)
The characterizations of survival potential of microorganisms which are able to thrive in extreme environments are receiving a great attention in astrobiological research as driven by the possibility of their existence in extraterrestrial extreme niches. Speculations about lithoautotrophic subsurface life on Mars are arising since ESA mission Mars Express determined water existence on Mars, fundamental requirement for life, and presence of CH4 in the Martian atmosphere, which could be originated only from active volcanism or from biological sources. Comparable conditions exist in permafrost regions on Earth.Methanogenic archaea, which colonized Siberian permafrost, are highly specialized organisms which can gain energy by the oxidation of H2 and use CO2 as the only carbon source. We present the investigations of resistance of methanogens from Siberian permafrost complementary to the already well-studied methanogens from non-permafrost habitats to different extreme life conditions of terrestrial or extraterrestrial permafrost: desiccation, temperature extremes, radiation, starvation, high salt concentration and simulated Mars conditions. The methanogenic archaea in pure cultures as well as in their natural environment of Siberian permafrost represent high survival potential under these extreme conditions. In contrast, these conditions were lethal for the reference organisms from non-permafrost habitats. Our data suggest that in scenario of subsurface lithoautotrophic life on Mars methanogenic archaea from Siberian permafrost could be used as appropriate candidates for possible life on Mars.